Penerapan Algoritma Hill Cipher dan Least Significant Bit (LSB) untuk Pengamanan Pesan pada Citra Digital - Desimeri Laoli; Bosker Sinaga; Anita Sindar R M Sinaga (JISKA (Jurnal Informatika Sunan Kalijaga), 2020)
Nowadays people exchange information in digital media such as text, audio, video and imagery. The development of Information and Communication makes the delivery of information and data more efficient. Current developments in technology which are very significant have an impact on the community in exchanging information and communicating. Confidential hidden data can also be in the form of image, audio, text, or video. The Hill Chiper algorithm uses a matrix of size m x m as a key for encryption and decryption. One way to recover the original text is of course to guess the decryption key, so the process of guessing the decryption key must be difficult. break ciphertext into palintext without knowing which key to use. The LSB part that is converted to the value of the message to be inserted. After affixing a secret message, each pixel is rebuilt into a whole image that resembles the original image media. The Hill Cipher algorithm is used to determine the position of the plaintext encryption into a random ciphertext. 2. Testing text messages using the hill cipher algorithm successfully carried out in accordance with the flow or the steps so as to produce a ciphertext in the form of randomization of the letters of the alphabet.